The chronic effects of a combination of herbal extracts (Euphytose®) on psychological mood state and response to a laboratory stressor: A randomised, placebo-controlled, double blind study in healthy humans. (November 2022) - Dodd, Fiona; Kennedy, David; Wightman, Emma; Khan, Julie; Patan, Michael; Elcoate, Rian; Jackson, Philippa
Background: Global lifetime prevalence of anxiety disorders has been estimated at approximately 16.6%, with subclinical prevalence likely much higher. Herbal approaches to reduce anxiety may be as effective as pharmacological treatments and are less likely to be associated with adverse side effects. The herbal species, namely, valerian, passionflower, hawthorn and ballota, have a long history of use as anxiolytics in traditional medicine, further supported by recent pre-clinical and clinical trials. Aims: To assess the effects of chronic (14 days) supplementation with a multi-herb extract preparation (MHEP, Euphytose ® ) on psychological state and psychological and physiological stress responses during a laboratory stressor. Methods: In this crossover study, 31 healthy participants (aged 19–58 years) received a MHEP and placebo for 14 days with a 28-day washout. Anxiety (State-Trait Anxiety Inventory), mood and physiological measures of stress (heart rate, galvanic skin response, salivary α-amylase and cortisol levels) were measured before and after an Observed Multitasking Stressor. Cognitive performance was also assessed. Results: MHEP was associated with reduced tension-anxiety ( p  = 0.038), with participants showing an attenuated response to the observed multitasking psychosocial stressor following MHEP, evidenced by lower salivary α-amylase ( p  = 0.041) and galvanic skin response ( p  = 0.004). Conclusions: The combination of herbal extracts contained within the MHEP reduced subjective anxiety in a healthy population and lowered electrodermal skin conductance and concentration of salivary α-amylase in response to a psychosocial stressor, compared to placebo. The study was registered on clinicaltrials.gov (identifier: NCT03909906).